(untitled) (The Agriculturists, 2014)
An experiment was conducted at the Horticulture farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during November 2010 to March 2011. Four levels of seedling tuber size, viz. 6-<7 g (S1), 7-<8 g (S2), 8-<9 g (S3) and, 9-?10 g (S4) and three levels of seedling tuber, viz. 1 hill-1 (N1), 2 hill-1 (N2) and 3 hill-1 (N3) were laid out in a Randomized Complete Block Design with three replications. At harvest, the tallest plant (82.17 cm), highest number of leaves plant-1 (83.30), highest LAI (6.23), tubers weight hill-1 (128.90 g) and tuber yield ha-1 (25.78 t) were found in S4, while the lowest was in S1. On the other hand, the tallest plant (74.91 cm), highest number of leaves plant-1 (74.45), highest LAI (5.41), tubers weight hill-1 (123.95 g) and tuber yield ha-1 (24.79 t) were found in N3, while the lowest was in N1. The tallest plant (85.09 cm), highest number of leaves plant-1 (87.97), highest LAI (6.64), tubers weight hill-1 (138.35 g) and tuber yield ha-1 (27.67 t) were found in S4N3 and the lowest gross tuber yield ha-1(12.83 t) was from S1N1. Large seedling tuber with single seedling tuber hill-1 performed better. DOI: http://dx.doi.org/10.3329/agric.v12i1.19866 The Agriculturists 2014; 12(1) 111-121